Experimental Study of Iraqi Light Naphtha Isomerization over Ni-Pt/H-Mordenite - Halah M. Hussain; Abdulhaleem A.K. Mohammed (Iraqi Journal of Chemical and Petroleum Engineering, 2019)
Hydroisomerization of Iraqi light naphtha was studied on prepared Ni-Pt/H-mordenite catalyst at a temperature range of 220-300°C, hydrogen to hydrocarbon molar ratio of 3.7, liquid hourly space velocity (LHSV) 1 hr-1 and at atmospheric pressure.